Fecal PCR survey and genome analysis of Lawsonia intracellularis in China - Wang, Lei; Wu, Wenqing; Zhao, Lifeng; Zhu, Zhanwei; Yao, Xinzhi; Fan, Jie; Chen, Hongjian; Song, Wenbo; Huang, Xi; Hua, Lin; Qian, Ping; Chen, Huanchun; et al. (Frontiers in Veterinary Science, 2024)
Proliferative enteropathy caused by Lawsonia intracellularis is an important economic associated disease to pig industry, but the knowledge about the prevalence of L. intracellularis in pig farms in China is limited. In addition, there is no complete genome sequence available for L. intracellularis isolates from China. In this study, we developed a TaqMan qPCR for the screening of L. intracellularis by targeting the bacterial 16S rDNA gene. Laboratory evaluations revealed a good sensitivity and specificity on detecting L. intracellularis nucleic acid. Using this method, we investigated 891 fecal samples from apparently healthy pigs in 47 farms. The results demonstrated a screening positive rate of 37.3% (95% CI, 34.1–40.5%) for the samples, and a farm screening positive rate of 93.6% (95% CI, 65.3–94.4%). The screening positive rate at herd level ranged from 6.67% (95% CI, 0.2–31.9%) to 40% (95% CI, 38–79.6%), while at animal level, the highest screening positive rate was found in 12-week-old pigs [85.7% (95% CI, 67.3–96.0%)]. Investigation of 705 diarrheal or bloody feces from symptomatic pigs revealed that the highest positive rate was found in replacement gilts which was 37.18% (95% CI, 45.1–89.5%). Secondly, we conducted the complete genome sequence of a L. intracellularis PPE-GX01-2022 from China through PacBio sequencing. The genome of PPE-GX01-2022 consisted of a chromosome of 1,439,110 bp in length and three plasmids of 193,063, 39,799, and 27,067 bp, respectively. This genome encoded 1,428 predicted proteins, 44 tRNAs, and 6 rRNAs. Sequence comparisons demonstrated that the genome sequence of PPE-GX01-2022 was highly homologous to those of two isolates from US, and these three isolates shared 1,378 core genes. The screening results suggest a high prevalence rate of L. intracellularis in Chinese pig farms. In addition, the genome sequence of the Chinese isolate was highly homologous to those of the field isolates from the US.